Annual Plan Proposals 1975-76 Department of Planning and Economic Affairs - Planning Commission (Planning Commission, 1975)
Planning in Kerala, in the context of the State’s peculiar socio-economic problems, has indeed been a formidable challenge. Though serious efforts have been made in the past to tackle these problems through the successive five year plans, the achievements in real terms have not been adequate. Industrial stagnation accompanied by a rapidly increasing population and the inflationary price trends that have been witnessed during the past years may be singled out, among other things, as the major retarding factors in the achievement of a satisfactory growth rate.
Department of Planning and Economic Affairs